2022
DOI: 10.18844/cjes.v17i8.7803
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis on bullying measurement models in schools

Abstract: Cases of bullying in schools are still a major problem in many countries and must be resolved immediately because they are closely related to student morale. So far, schools are still focused on strategies to overcome bullying, but have not focused on exploring the right measurement model to identify bullying. This study aims to identify bullying systematically in schools. This is a quantitative research using principal component analysis (PCA). The questionnaire was developed based on the findings of previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thus, based on this research, the CFS policy evaluation instrument in elementary schools can reflect the conditions for implementing CFS policies. The goodness of fit is to see the fit of the model; this study found that all indicators of the goodness of fit model (p-value, RMSEA, GFI, AGFI) have been met, and the model is acceptable or fit, so overall, it shows that the theoretical model is by the empirical data that has been tested (Herwin & Nurhayati, 2021;Nurhayati et al, 2022). A measuring instrument is declared to have a high-reliability coefficient if it can provide consistent and stable measurement results when measurements are taken; this indicates that the measurement results have a slight error rate (Otaya et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, based on this research, the CFS policy evaluation instrument in elementary schools can reflect the conditions for implementing CFS policies. The goodness of fit is to see the fit of the model; this study found that all indicators of the goodness of fit model (p-value, RMSEA, GFI, AGFI) have been met, and the model is acceptable or fit, so overall, it shows that the theoretical model is by the empirical data that has been tested (Herwin & Nurhayati, 2021;Nurhayati et al, 2022). A measuring instrument is declared to have a high-reliability coefficient if it can provide consistent and stable measurement results when measurements are taken; this indicates that the measurement results have a slight error rate (Otaya et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Another unit of analysis is the validity of the CFS evaluation instrument by looking at the results of the loading factor on each indicator; the contribution of the loading factor on all indicators, both context, input, process, and product, all obtained a value of more than .50 which indicates that all measuring items that build CFS policy evaluation instruments have been able to measure their indicators significantly (Nurhayati et al, 2022). This is by the measurement point of view, which states that construct validity shows the extent to which the instrument can see or measure the aspects to be measured (Herwin & Nurhayati, 2021); this is also following the exposure (Otaya et al, 2020), which states that construct validity is used to prove that the instrument made is proven valid in terms of its construct.…”
Section: Discussionmentioning
confidence: 99%